Incoherent excitation and switching of spin states in exciton-polariton condensates - Liew, Timothy Chi Hin (2015)
We investigate, theoretically and numerically, the spin dynamics of a two-component exciton-polariton condensate created and sustained by nonresonant spin-polarized optical pumping in a semiconductor microcavity. Using the open-dissipative mean-field model, we show that the existence of well defined phase-locked steady states of the condensate may lead to efficient switching and control of spin (polarization) states with a nonresonant excitation. Spatially inhomogeneous pulsed excitations can cause symmetry breaking in the pseudospin structure of the condensate and lead to formation of nontrivial spin textures. Our model is universally applicable to two linearly coupled polariton condensates, and therefore can also describe the behavior of condensate populations and phases in “double-well” type potentials.